ANALISIS KINERJA KEUANGAN PT. MAYORA INDAH TBK PERIODE 2022–2024 - Bonefasius Radit Doulet; Regina Pribadi; Dyah Rini Prihastuty (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study aims to analyze the financial performance of PT. Mayora Indah Tbk during the 2022–2024 period using key financial ratios, including liquidity, solvency, activity, and profitability ratios. The data were obtained from the company’s annual financial statements published on its official website and the Indonesia Stock Exchange. The results show that PT. Mayora Indah Tbk maintains strong liquidity, a relatively stable solvency structure, consistent asset utilization efficiency, and profitability that fluctuates but remains within a reasonable range for the food and beverage industry. Overall, the company demonstrates good financial performance, although the decline in profitability and return on equity in 2024 should be addressed by management to improve operational efficiency and cost control.